1997
DOI: 10.1038/sj.onc.1200915
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of an approximately 1.5 Mb DNA segment at chromosome 5q22 indicates the locus of a new tumour gene in nonpapillary renal cell carcinomas

Abstract: Previous karyotyping showed an unbalanced translocation between chromosome 3p11.2-p13 and chromosome 5q22 leading to duplication of chromosome 5q22-qter region in nonpapillary renal cell carcinomas. In order to determine the breakpoint at chromosome 5q22 at the molecular level, we have investigated 50 sporadic nonpapillary renal cell carcinomas from consecutive nephrectomies and 24 renal cell carcinomas obtained from two patients with von Hippel ± Lindau disease. We used seven DNA markers mapped to and around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…It has indeed been proposed that allelic imbalances on 17q could in some cases correspond to gains (Devilee et al, 1991). Furthermore, recent work has shown that allelotyping based on CA repeat analysis has been used successfully in amplicon mapping of tumors known to be ampli®ed at 12q13 (Wolf et al, 1997), as well as in characterizing chromosome duplication (Bugert et al, 1998;Kenck et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has indeed been proposed that allelic imbalances on 17q could in some cases correspond to gains (Devilee et al, 1991). Furthermore, recent work has shown that allelotyping based on CA repeat analysis has been used successfully in amplicon mapping of tumors known to be ampli®ed at 12q13 (Wolf et al, 1997), as well as in characterizing chromosome duplication (Bugert et al, 1998;Kenck et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown duplication of chromosome 5q22 region by RFLP analysis in about 70% of non-papillary RCCs in another series (Kenck et al, 1997). Two of these tumors (HA314, HA324) showed a small duplication with the proximal breakpoint between the apc and mcc genes and the distal end between loci D5S1170 and D5S81 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We also confirmed the allelic duplication at chromosome 5q22-qter region and detected an interstitial duplication of approx. 1.5-2 Mb DNA segment including the mcc gene at the chromosome 5q22 by Southern blotting and FISH analysis (Kovacs and Kung, 1991;Kenck et al, 1997). The breakpoints involved in translocation 3;5 as well as the breaks at the proximal end of the interstitial duplication were mapped between the apc and mcc genes.…”
Section: Wiley-liss Incmentioning
confidence: 99%
“…Loss of chromosome 14q and gain of chromosome 5q, considered either individually or together, are seen more often in kidney cancer than in other cancers and presumably reflect selection pressure to silence one or more 14q kidney cancer suppressor genes and to increase the expression of one or more 5q kidney cancer oncogenes (Shen et al, 2011). Interestingly, unbalanced translocations involving chromosomes 3p and 5q, including constitutional translocations, have been reported in kidney cancer that result in loss of chromosome 3p and gain of 5q (Bos et al, 1998; Iqbal et al, 1996; Kenck et al, 1997; Kovacs et al, 1991; Kovacs and Frisch, 1989; Kovacs and Kung, 1991; Kovacs et al, 1987; Presti et al, 1991). …”
Section: Introductionmentioning
confidence: 99%